Pengaruh degree of fundamental leverage, beta saham, tingkat pertumbuhan, roe, dan size terhadap price to book value (pbv) pada perusahaan manufaktur di bursa efek indonesia tahun 2010-2011 - Tengku Fadilla Arbaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study was to analyze the effect of Degree of Financial Leverage, stock beta / beta risk, rate of growth, ROE against Price To Book Value (PBV) and the effect size against Price To Book Value (PBV) in manufacturing companies in Indonesia Stock Exchange in 2010 -2011.The population was 164 manufacturing companies, while in the sample using purposive sampling method based on specific criteria, so that only 68 companies that meet thecriteria.The study states that the financial leverage and size showed a positive relationship, but did not significantly affect the PBV. Beta risk and growth rate showed a negative relationship and significantly affect the PBV. ROE shows a positive and significant effect on PBV. The coefficient of determination obtained amounted to 0.342 or 34.20% mean PBV in manufacturing companies at 34.20% explained by financial leverage, beta risk, rate of growth, ROE and the remaining 65.80% influenced by other variables such as dividend policy, liquidity, solvency, etc., which are not examined in this study.Keywords: Degree of Financial Leverage, Beta, Growth, Return On Equity, Price To Book Value